Guidelines on pediatric day surgery of the Italian Societies of Pediatric Surgery (SICP) and Pediatric Anesthesiology (SARNePI) - Ugo de Luca; Giovanni Mangia; Simonetta Tesoro; Ascanio Martino; Maria Sammartino; Alessandro Calisti (BMC, 2018)
Abstract The Italian Society of Pediatric Surgery (SICP) together with The Italian Society of Pediatric Anesthesia (SARNePI) through a systematic analysis of the scientific literature, followed by a consensus conference held in Perugia on 2015, have produced some evidence based guidelines on the feasibility of day surgery in relation to different pediatric surgical procedures. The main aspects of the pre-operative assessment, appropriacy of operations and discharge are reported.